Cardiovascular Complications of Prostate Cancer Treatment - Wilk, Michał; Waśko-Grabowska, Anna; Szmit, Sebastian (Frontiers in Pharmacology, 2020)
Treatment of prostate cancer (PC) is a rapidly evolving field of pharmacology research. In recent years, numerous novel therapeutics that improve survival and ameliorate disease control have been approved. Currently, the systemic treatment for prostate neoplasm consists of hormonal therapy, chemotherapy, immunotherapy, radiopharmaceuticals, targeted therapy, and supportive agents (e.g., related to bone health). Unfortunately, many of them carry a risk of cardiovascular complications, which occasionally pose a higher mortality threat than cancer itself. This article provides a unique and comprehensive overview of the prevalence and possible mechanisms of cardiovascular toxicities of all PC therapies, including state-of-the-art antineoplastic agents. Additionally, this article summarizes available recommendations regarding screening and prevention of the most common cardiac complications among patients with advanced cancer disease.